The spectroscopic and transition properties of ZnHe: MRCI+Q study including spin-orbit coupling. (March 2023) - Li, Lulu; Li, Chao; Yan, Bing
Highlights: MRCI+Q calculations are performed on ZnHe including spin-orbit coupling effect. Potential energy curves and spectroscopic constants for bound states of ZnHe are obtained. The TDM of A 3 Π0+ -X 1 Σ + 0+, B 3 Π1 -X 1 Σ + 0+, c 3 Σ + 1 -X 1 Σ + 0+, C 1 Π1 -X 1 Σ + 0+ and D 1 Σ + 0+ -X 1 Σ + 0+ transitions of ZnHe are analyzed. Franck-Condon factors (FCFs) and radiative lifetimes of the transitions A 3 Π0+ -X 1 Σ + 0+ and C 1 Π1 -X 1 Σ + 0+ are reported. Abstract: A high level ab initio study on electronic states of ZnHe is carried out by utilizing multireference configuration interaction plus Davidson correction (MRCI+Q) method. The potential energy curves (PECs) of the 9 Λ-S states and the 18 Ω states generated from the Λ-S states after considering the spin-orbit coupling (SOC) effects are computed. Based on the computed potential energy curves, the spectroscopic constants of the bound states of ZnHe are acquired, which are in accordance with the previous theoretical results. The transition properties including dipole moments (DMs) of the Λ-S states, transition dipole moments (TDMs), the vibrational band origins, rotational constants, Franck-Condon factors (FCFs) and the radiative lifetimes of some low-lying states have also been acquired. Comparisons with the available previous works are made. This work give a comprehensive picture of PECs and transition properties for transitions between low-lying excited states and ground state, such as A 3 Π0+ -X 1 Σ + 0+ and C 1 Π1 -X 1 Σ + 0+, and should enhance our understanding on the electronic structure and spectroscopy of ZnHe molecule. Graphical abstract: Image, graphical abstract "Large" SO matrices comprising all molecular states considered are formed according to symmetry and diagonalized for each case to generate the appropriate SO potential energies. the SO interaction has a great influence on the Ω states correlating with different fine-structure components of the Zn (4s4p) triplet state.